ANTIOXIDANT STATUS AND TUBER YIELD IN DIFFERENT POTATO CULTIVARS - Singh, R. K.; Marwaha, R S.; Sharma, Jyotsana; Singh, Sarjeet (Potato Journal, 2013)
Tubers of 11 potato cultivars were evaluated for 3 antioxidants, viz., carotenoids, ascorbic acid and total phenols. Hybrid JH-214 recorded highest carotenoid content (110.9 mg per 100g fresh tuber weight) as compared to 30.9 to 80.9 mg in other cultivars. Ascorbic acid, although, was numerically maximum in Kufri Chandramukhi (16.9 mg), was statistically at par with hybrid JH-214, Kufri Jyoti and Kufri Ashoka. Total phenols were highest in Kufri Jyoti (67.4 mg) followed by Kufri Chandramukhi (51 mg). While,Kufri Ashoka, Kufri Lauvkar, Kufri Sutlej and hybrid JH-214, showed no significant differences (46-46.9 mg). Yield trial of hybrid JH-214 was carried out with Kufri Jyoti and Kufri Ashoka. Hybrid JH-214 was far superior to control varieties Kufri Jyoti and Kufri Ashoka in the production of seed size tubers (5.6 x 105ha), total tubers (9.1 105/ha) and rate of multiplication on number basis (10.9 times).